Adsorbent and application thereof in prolonging service life of catalyst

By using modified adsorbents, including concave and convex rod earth, electrical stone powder, diatomaceous earth and sepiolite powder, the coke and toxic substances generated during the synthesis process, the problem of the catalyst's short service life in the synthesis of o-cresol and 2,6-dicresol is solved, and the catalyst's life is significantly extended.

CN119657074APending Publication Date: 2025-03-21NANTONG XINGCHEN SYNTHETIC MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411863573.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing catalysts do not have long service life in the synthesis of o-cresol and 2,6-dicresol, and are prone to inactivation due to high temperatures such as lattice changes, coking and material poisoning.

Method used

An adsorbent is used, which includes concave and convex rod soil, electrical stone powder, diatomaceous earth and sepirofoam powder, and its adsorption performance is improved by modification treatment. The adsorbent can adsorb cokes or polymers produced by methanol, phenol, o-cresol and 2,6-dicresol, as well as trace amounts of toxic materials in the material, thereby extending the service life of the catalyst.

Benefits of technology

It effectively extends the service life of the catalyst, which is manifested in that under the same conditions, the life of the catalyst is extended from the original 5 months to more than 8 months.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of catalytic reaction, in particular to an adsorbent and application thereof in prolonging the service life of a catalyst. The adsorbent is prepared from the following raw material components in parts by mass: 30 to 88 parts of attapulgite, 10 to 50 parts of electric appliance stone powder, 0 to 20 parts of diatomite and 1 to 20 parts of sepiolite powder. The adsorbent provided by the invention can adsorb coked materials or polymers generated by methanol, phenol, o-cresol and 2, 6-xylenol and trace toxic materials entrained in the materials under a high-temperature condition; and the service life of the catalyst for synthesizing o-cresol and 2, 6-xylenol is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalytic reaction, and in particular to an adsorbent and an application thereof in improving the life of a catalyst. Background Art

[0002] o-Cresol and 2,6-dimethylphenol are important chemical synthesis raw materials: o-Cresol is an important raw material for synthesizing antioxidants, plastic fillers, disinfectants and o-Cresol epoxy resin. 2,6-dimethylphenol is an important raw material for synthesizing tetramethyl bisphenol F and polyphenylene ether. The raw materials for synthesizing o-Cresol and 2,6-dimethylphenol are phenol and methanol. There are many catalysts. The current mainstream catalysts include magnesium-based catalysts with magnesium oxide as the main component, iron-vanadium catalysts with iron oxide and vanadium oxide as the main component, and iron-chromium-based catalysts with iron oxide and chromium oxide as the main component. However, the service life of all catalysts is not very long, and the longest time is no more than 6 months. The reasons for deactivation include: deactivation due to high-temperature catalyst lattice change, phenol and methanol, especially o-Cresol and 2,6-dimethylphenol in phenol, are more likely to coke during the preheating process, causing the material catalyst bed to deviate or not flow, causing deactivation, and the presence of sulfur, phosphorus and chlorine in the material causing catalyst poisoning and deactivation.

[0003] The deactivation of high-temperature catalysts due to lattice changes has been determined to be unchangeable at the beginning of catalyst design. In order to increase the life of the catalyst, catalyst suppliers have adopted various methods: 1. Adding oxides or carbonates of alkali metals or alkaline earth metals during the catalyst synthesis process or in the finished catalyst (alkali metals or alkaline earth metals decompose the coke around the catalyst under high temperature conditions) to extend the life of the catalyst. The service life of the catalyst has increased compared to the original, but the maximum life of the catalyst is no more than 6 months. 2. Changing the reaction shape, making the catalyst into a ring or sphere, but the material does not stay on the catalyst surface for a long time and the reaction content is low. None of the above schemes have played a significant role.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides an adsorbent and its application in improving the life of a catalyst.

[0006] Specifically, the technical solution of the present invention is as follows: In a first aspect, the present invention provides an adsorbent comprising the following raw material components in parts by weight: 30-88 parts of attapulgite, 10-50 parts of electroplated stone powder, 0-20 parts of diatomaceous earth, and 1-20 parts of sepiolite powder.

[0007] Preferably, the adsorbent comprises the following raw material components in parts by weight: 63-80 parts of attapulgite, 8-15 parts of electroplated stone powder, 5-12 parts of diatomaceous earth, and 5-12 parts of sepiolite powder.

[0008] Preferably, the total amount of each raw material component of the adsorbent is 100 parts.

[0009] In a second aspect, the present invention provides a method for preparing the adsorbent, comprising the steps of: mixing each raw material component with water, stirring into a mass and drying, and then placing in a 400-600°C environment for 4-8 hours; preferably placing in a 450-550°C environment for 4 hours.

[0010] Preferably, the drying temperature after stirring into agglomeration is 150-280°C, preferably 180-250°C; and the drying time is 2±0.5h.

[0011] Preferably, after being stirred into a mass, the mixture is squeezed into Φ3-5 strips and air-dried for 8±2 hours, and then placed in a drying oven at 150-280° C. for 2±0.5 hours.

[0012] Preferably, the attapulgite is first treated by vacuum immersion in hydrochloric acid and then mixed with other raw materials; the concentration of hydrochloric acid is 1%-5%; the vacuum immersion time is 1-12 hours, preferably 8-12 hours.

[0013] Preferably, the tourmaline powder is first prepared into a slurry with deionized water, and then mixed with other raw materials through ultrasonic oscillation treatment; the ultrasonic power is 40-200kHz, preferably 50-120kHz; the oscillation time is 1-12h, preferably 8±2h.

[0014] In a third aspect, the present invention provides use of the adsorbent or the adsorbent prepared by the preparation method in improving the life of a catalyst.

[0015] Preferably, the catalyst is used for catalytic synthesis of o-cresol and 2,6-dimethylphenol.

[0016] Beneficial effects: The present invention provides an adsorbent and its application for improving the life of a catalyst. The adsorbent of the present invention comprises the following raw material components by weight: 30-88 parts of attapulgite, 10-50 parts of electrical stone powder, 0-20 parts of diatomaceous earth, and 1-20 parts of sepiolite powder. The adsorbent provided by the present invention can adsorb methanol, phenol, o-cresol and 2,6-dimethylphenol to produce coke or polymer, as well as trace toxic materials entrained in the materials under high temperature conditions; and improve the service life of the catalyst for synthesizing o-cresol and 2,6-dimethylphenol. DETAILED DESCRIPTION

[0017] The present invention provides an adsorbent capable of adsorbing coke or polymer produced by methanol, phenol, o-cresol and 2,6-dimethylphenol under high temperature conditions, as well as trace amounts of toxic materials entrained in the materials, and a preparation method and application thereof. When the adsorbent is used, a material purifier (with adsorbent inside) is added before the reaction to adsorb coke, polymer and substances in the material that are toxic to the catalyst produced during the heating process of the material.

[0018] In a more preferred and specific embodiment, the adsorbent provided by the present invention for adsorbing coke or toxic substances in the reaction materials for producing o-cresol and 2,6-xylenol is prepared from the following raw materials by weight percentage: attapulgite: 30%-88%; electrical stone powder: 10-50%; diatomaceous earth: 0-20%; sepiolite powder: 1-20%.

[0019] In a more preferred and specific embodiment, the adsorbent preparation method comprises the following steps: Step 1: Modification of attapulgite: Take 20-90um attapulgite, add 300%-400% hydrochloric acid (1-5%) of the attapulgite amount, vacuum soak for 1-12 hours, wash and filter until the pH is 7, and place the filter cake for later use.

[0020] Step 2: Tourmaline powder modification: Take 20-90um tourmaline powder, mix it with deionized water (30%-40% of the undetermined amount of tourmaline powder) to make a slurry, put it into an ultrasonic processing tank and vibrate it under 40-200kHz ultrasonic waves for 1-12 hours. Set aside for later use.

[0021] Step 3: Mix the materials prepared in the first and second steps, add diatomaceous earth and sepiolite powder, and stir into a mass.

[0022] Step 4: Use an extruder to extrude the prepared mass into strips of Φ3-5mm and air dry them.

[0023] Step 5: Place the dried strips into a muffle furnace and calcine at 400-600°C for 4-8 hours to prepare an adsorbent.

[0024] The present invention mainly takes advantage of the fact that attapulgite can adsorb some high-boiling point compounds in gas at high temperature, including heavy metals and sulfides. In particular, after being modified, its adsorption performance can be significantly improved.

[0025] The present invention utilizes the spontaneous polarization characteristics of electrical stone powder at high temperature to create an electrostatic field around it, and has strong adsorption properties, which can effectively adsorb charged ions, such as chloride ions and chlorine-containing compounds (chloride ions are one of the main reasons for the deactivation of iron-based catalysts), thereby increasing the life of the catalyst.

[0026] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] The endpoints and any values ​​of the ranges disclosed in this specification are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0028] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "specific implementations", or "some specific implementations" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the embodiment of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0029] In the examples provided in this specification, if no specific techniques or conditions are specified, the techniques or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased through regular channels.

[0030] Example 1 This embodiment provides an adsorbent, and its raw material formula is: 100 grams of 20-90um attapulgite, 20 grams of 20-90um tourmaline powder, 9 grams of diatomaceous earth, and 16 grams of sepiolite powder.

[0031] This embodiment provides a method for preparing the above-mentioned adsorbent, comprising the following steps: (1) Take 100 g of 20-90 μm attapulgite, add 300 g of hydrochloric acid (2%) and soak in vacuum for 12 hours, wash and filter until the pH is 7, and set the filter cake aside for later use.

[0032] (2) Take 20g of 20-90um tourmaline powder, mix it with 6g of deionized water to make a slurry, put it into an ultrasonic processing tank and vibrate it under 120kHz ultrasonic wave for 8 hours. Set aside for later use.

[0033] (3) After mixing the two, add 9 g of diatomaceous earth and 16 g of sepiolite powder and stir into a dough. Use an extruder to extrude into Φ5 strips and air-dry for 8 hours.

[0034] (4) The dried strips were placed in a muffle furnace and dried at 180°C for 2 hours, and then heated to 500°C and dried for 4 hours to prepare an adsorbent.

[0035] Example 2 This embodiment provides an adsorbent, and its raw material formula is: 100 grams of 20-90um attapulgite, 12 grams of 20-90um tourmaline powder, 14 grams of diatomaceous earth, and 8 grams of sepiolite powder.

[0036] This embodiment provides a method for preparing the above-mentioned adsorbent, comprising the following steps: (1) Take 100 g of 20-90 μm attapulgite, add 400 g of hydrochloric acid (3%), soak in vacuum for 8 hours, wash and filter until the pH is 7, and set the filter cake aside for later use.

[0037] (2) Take 12g of 20-90um tourmaline powder, mix it with 6g of deionized water to make a slurry, put it into an ultrasonic processing tank and vibrate it under 50kHz ultrasonic wave for 8 hours. Set aside for later use.

[0038] (3) After mixing the two, add 14 g of diatomaceous earth and 8 g of sepiolite powder and stir into a dough. Use an extruder to extrude into Φ5 strips and air-dry for 8 hours.

[0039] (4) The dried strips were placed in a muffle furnace and dried at 180°C for 2 hours, and then heated to 500°C and dried for 4 hours to prepare an adsorbent.

[0040] Example 3 This embodiment provides an adsorbent, and its raw material formula is the same as that of Example 2.

[0041] This embodiment provides a method for preparing the above-mentioned adsorbent, comprising the following steps: (1) Take 100 g of 20-90 μm attapulgite, add 300 g of hydrochloric acid (1%) and soak in vacuum for 8 hours, wash and filter until the pH is 7, and set the filter cake aside for later use.

[0042] (2) Take 12g of 20-90um tourmaline powder, mix it with 5g of deionized water to make a slurry, put it into an ultrasonic processing tank and vibrate it under 50kHz ultrasonic wave for 8 hours. Set aside for later use.

[0043] (3) After the two are mixed evenly, add 14 grams of diatomaceous earth and 8 grams of sepiolite powder and stir into a dough. Use an extruder to extrude into Φ5 strips and dry them for 8 hours.

[0044] (4) The dried strips were placed in a muffle furnace and dried at 250°C for 2 hours, and then heated to 550°C and dried for 4 hours to prepare an adsorbent.

[0045] Example 4 This embodiment provides an adsorbent, and its raw material formula is: 100 grams of 20-90um attapulgite, 20 grams of 20-90um tourmaline powder, 14 grams of diatomaceous earth, and 8 grams of sepiolite powder.

[0046] This embodiment provides a method for preparing the above-mentioned adsorbent, comprising the following steps: (1) Mix 100 g of 20-90 um attapulgite, 20 g of 20-90 um tourmaline powder, 14 g of diatomaceous earth, and 8 g of sepiolite powder evenly, add 40 g of deionized water, and stir into a dough. Use an extruder to extrude into Φ5 strips and air-dry for 8 hours.

[0047] (2) The dried strips were placed in a muffle furnace and dried at 250°C for 2 hours, and then heated to 550°C and dried for 4 hours to prepare an adsorbent.

[0048] Experimental Example 1 In this experimental example, the adsorbent provided in Examples 1-4 was loaded into a reactor for evaluation. The specific operation was as follows: a fixed bed reactor with a reaction tube having an inner diameter of 20 mm was loaded with 100 ml of Φ5*5 catalyst prepared by patent CN1634656 at the bottom and a ceramic ring or 30 grams of adsorbent prepared in Examples 1-4 at the top. The reactor outlet pressure was controlled at 0.2 MPa, the molten salt temperature was 350°C and the liquid space velocity was 1.0 h -1 , o-cresol and 2,6-dimethylphenol were synthesized under the condition of a material ratio of phenol:methanol:water = 1:3:2.8.

[0049] Responses were evaluated for 30 days.

[0050] The experimental data after catalyst disassembly are shown in Table 1.

[0051] Table 1 From the above data, it can be seen that the addition of each adsorbent has no significant effect on the catalyst activity and selectivity. The adsorbent in Example 1 has a better adsorption effect.

[0052] Experimental Example 2 In this experimental example, the adsorbent provided in Example 1 was loaded into a reactor for evaluation. The specific operation was as follows: a fixed bed reactor with a reaction tube having an inner diameter of 20 mm was loaded with 100 ml of Φ5*5 catalyst prepared by patent CN1634656 at the bottom and a ceramic ring or 30 grams of adsorbent prepared by Example 1 at the top. The reactor outlet pressure was controlled at 0.2 MPa, the molten salt temperature was 350°C and the liquid space velocity was 1.0 h -1 , o-cresol and 2,6-dimethylphenol were synthesized under the condition of a material ratio of phenol:methanol:water = 1:3:2.8.

[0053] Responses were evaluated at 8 months.

[0054] The data after catalyst disassembly are shown in Table 2.

[0055] Table 2 From the above data, we can see that the life of the catalyst is about 5 months when ceramic rings are added before the catalyst bed, while the life of the catalyst can be extended to more than 8 months when adsorbent is added before the catalyst bed.

[0056] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. An adsorbent, characterized in that The invention comprises the following raw material components in parts by weight: 30-88 parts of attapulgite, 10-50 parts of electroplating stone powder, 0-20 parts of diatomite and 1-20 parts of sepiolite powder.

2. The adsorbent according to claim 1, characterized in that: The invention comprises the following raw material components in parts by weight: 63-80 parts of attapulgite, 8-15 parts of electroplating stone powder, 5-12 parts of diatomite and 5-12 parts of sepiolite powder.

3. The adsorbent according to claim 1 or 2, characterized in that: The total amount of each raw material component is 100 parts.

4. The method for preparing the adsorbent according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: mixing various raw material components with water, stirring into agglomerates, drying, and then placing in a 400-600° C. environment for 4-8 hours; preferably placing in a 450-550° C. environment for 4 hours.

5. The method for preparing the adsorbent according to claim 4, characterized in that: The drying temperature after stirring into agglomeration is 150-280°C, preferably 180-250°C; the drying time is 2±0.5h.

6. The method for preparing the adsorbent according to claim 4 or 5, characterized in that: After stirring into a dough, squeeze it into Φ3-5 strips and dry it for 8±2 hours, then place it in a drying oven at 150-280℃ for 2±0.5h.

7. The method for preparing the adsorbent according to any one of claims 4 to 6, characterized in that: The attapulgite is firstly treated by vacuum soaking in hydrochloric acid and then mixed with other raw materials; the concentration of hydrochloric acid is 1%-5%; the vacuum soaking time is 1-12h, preferably 8-12h.

8. The method for preparing the adsorbent according to any one of claims 4 to 7, characterized in that: The tourmaline powder is first prepared into a slurry with deionized water, and then mixed with other raw materials after ultrasonic oscillation treatment; the ultrasonic power is 40-200kHz, preferably 50-120kHz; the oscillation time is 1-12h, preferably 8±2h.

9. Use of the adsorbent according to any one of claims 1 to 3 or the adsorbent prepared by the preparation method according to any one of claims 4 to 8 in improving the life of a catalyst.

10. The use according to claim 9, characterized in that: The catalyst is used for catalytic synthesis of o-cresol and 2,6-dimethylphenol.